Demand of sports and leisure for youth in the city of Novo Hamburgo, Brazil - SANFELICE, GUSTAVO ROESE; JAHN, ELENARA; DALZOCHIO, THAÍS (Revista Latinoamericana de Ciencias Sociales, Niñez y Juventud, 2013)
(analytical): The adult and elderly population of Brazil has increased recently and the country has directed public policies which are in accordance with its demands. Youth have been neglected in specific public policies, in particular when considering the sports and leisure needs. Thus, we aimed to identify the demand for sports and leisure by young people in the city of Novo Hamburgo, Brazil. Sixty young answered a structured questionnaire in 2010, of these, 34.7% answered they need more time for their activities, 30.4% need more infrastructure and 15.3% seek more accessible spaces. Although Novo Hamburgo presents projects and actions in the scope for sports and leisure for this age-group, the projects do not include all young people, but rather a small part, and as such this is considered to be a state of social vulnerability.